Atypical Expression of Smooth Muscle Markers and Co-activators and Their Regulation in Rheumatic Aortic and Calcified Bicuspid Valves - Latif, Najma; Sarathchandra, Padmini; McCormack, Ann; Yacoub, Magdi H.; Chester, Adrian H. (Frontiers in Cardiovascular Medicine, 2022)
Objective: We have previously reported that human calcified aortic valves have abundant expression of smooth muscle (SM) markers and co-activators. We hypothesised that cells in bicuspid aortic valve (BAV) and those affected by rheumatic valve (RV) disease may follow a similar phenotypic transition into smooth muscle cells, a process that could be regulated by transforming growth factors (TGFs). Aims: Cusps from 8 patients with BAV and 7 patients with RV were analysed for ealy and late SM markers and regulators of SM gene expression by immunocytochemistry and compared to healthy aortic valves from 10 unused heart valve donors. The ability of TGFs to induce these markers in valve endothelial cells (VECs) on two substrates was assessed. Results: 7 out of 8 BAVs and all the RVs showed an increased and atypical expression of early and late SM markers α-SMA, calponin, SM22 and SM-myosin. The SM marker co-activators were aberrantly expressed in 6 of the BAV and 6 of the RV, in a similar regional pattern to the expression of SM markers. Additionally, regions of VECs and endothelial cells lining the vessels within the cusps were found to be positive for SM markers and co-activators in 3 BAVs and 6 RV. Fibronectin was shown to be upregulated in bicuspid and rheumatic cusps, within the cusps as well as in the basement membrane. The ability of TGFβs to induce the expression of SM markers and myocardin was greater in VECs cultured on fibronectin than on gelatin. Conclusion: BAV and RV expressed increased numbers of SM marker-positive VICs and VECs. Concomittantly, these cells expressed MRTF-A and myocardin, key regulators of SM gene expression. TGFβ1 was able to preferentially upregulate SM markers and myocardin in VECs on fibronectin, and fibronectin was found to be upregulated in BAV amd RV. These findings suggest a role of VEC as a source of cells that express SM cell markers in BAV and RV. The similarity between SM marker expression in BAV and RV with our previous study with cusps from patients with aortic stenosis suggests the existance of a common pathological pathway between these different pathologies.